Statistical Analysis on Detecting Recombination Sites in DNA-β Satellites Associated with Old World Geminiviruses - Xu, Kai; Yoshida, Ruriko (Frontiers in Psychiatry, 2010)
Although exchange of genetic information by recombination plays an important role in the evolution of viruses, it is not clear how it generates diversity. Understanding recombination events helps with the study of the evolution of new virus strains or new viruses. Geminiviruses are plant viruses which have ambisense single-stranded circular DNA genomes and are one of the most economically important plant viruses in agricultural production. Small circular single-stranded DNA satellites, termed DNA-beta, have recently been found to be associated with some geminivirus infections. In this paper we analyze several DNA-beta sequences of geminiviruses for recombination events using phylogenetic and statistical analysis and we find that one strain from ToLCMaB has a recombination pattern and is a recombinant molecule between two strains from two species, PaLCuB-[IN:Chi:05] (major parent) and ToLCB-[IN:CP:04] (minor parent). We propose that this recombination event contributed to the evolution of the strain of ToLCMaB in South India. The Hidden Markov Chain (HMM) method developed by Wedd et al estimating phylogenetic tree through out the whole alignment provide us a recombination history of these DNA-beta strains. It is the first time that this statistic method has been used on DNA-beta recombination study and give a clear recombination history of DNA-beta recombination.